2019
DOI: 10.3389/fneur.2019.00713
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy: A Brief Overview

Abstract: Chronic Traumatic Encephalopathy (CTE) is a debilitating neurodegenerative disease, which has been increasingly reported in athletes, especially American football players, as well as military veterans in combat settings, commonly as a result of repetitive mild traumatic brain injuries (TBIs). CTE has a unique neuropathological signature comprised of accumulation of phosphorylated tau (p-tau) in sulci and peri-vascular regions, microgliosis, and astrocytosis. As per most recent disease classification, the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…However, the neuronal p-tau found in CTE does share a similar profile regarding isoform ratio and phosphorylation state as the tau in AD (10). Both CTE and AD share the characteristic feature of hyperphosphorylated tau, where phosphorylation at specific residues occurs as an ordered process, leading to tau aggregation and oligomer formation (6). However, in the present case, the severity of CA1-predominant neurofibrillary degeneration in the hippocampus supports the coexistence of AD and CTE (10,22).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, the neuronal p-tau found in CTE does share a similar profile regarding isoform ratio and phosphorylation state as the tau in AD (10). Both CTE and AD share the characteristic feature of hyperphosphorylated tau, where phosphorylation at specific residues occurs as an ordered process, leading to tau aggregation and oligomer formation (6). However, in the present case, the severity of CA1-predominant neurofibrillary degeneration in the hippocampus supports the coexistence of AD and CTE (10,22).…”
Section: Discussionsupporting
confidence: 52%
“…In 2016, the first NINDS/NIBIB consensus meeting defined the neuropathological criteria of CTE and confirmed that the pathognomonic lesions in CTE are accumulations of abnormally hyperphosphorylated tau (p-tau) in astrocytes and neurons located around small blood vessels and at the depths of the cortical sulci (10). CTE, a new neurodegenerative tauopathy, was reported in athletes who played soccer, baseball, ice hockey, and rugby, as well as in military personnel exposed to explosive blasts (5)(6)(7)11). Clinical presentation of CTE was divided into three phases: behavioral/psychiatric, cognitive, and motor (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug is therefore not ideal for AD treatment. On the other hand, it has been reported that a spike of tau hyperphosphorylation happens after brain injury 76 and general anesthesia 77 , due likely to acutely diminished phosphatase activities 78,79 . Whether this transient tau hyperphosphorylation is related to the positive association between dementia and traumatic brain injury 13 or exposure to general anesthesia 80 remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…For example, moderate or severe TBI contributes to the development of late-onset neurodegenerative diseases, in particular AD and PD (Mendez, 2017). Chronic traumatic encephalopathy (CTE), a condition that shares features with neurodegenerative diseases, is linked to mild TBI (Fesharaki-Zadeh, 2019). Numerous random-effects meta-analysis (Perry et al, 2016), epidemiologic study (Gardner and Yaffe, 2015), and retrospective cohort study (Gardner et al, 2018) have lent support to these associations.…”
Section: Introductionmentioning
confidence: 99%